Whole-Field Sequential Intensity–Modulated Radiotherapy for Local-Regional Advanced Head-and-Neck Squamous Cell Carcinoma. (December 2015) - Refaat, Tamer; Choi, Mehee; Thomas, Tarita O.; Bacchus, Ian; Agulnik, Mark; Pelzer, Harold J.; Mellott, Ann L.; Rademaker, Alfred W.; Liu, Dachao; Sathiaseelan, Vythialinga; Mittal, Bharat B.
Abstract : Purpose: There is little published data on the technique and results of whole-field (WF) sequential intensity–modulated radiotherapy (S-IMRT) for patients with head-and-neck squamous cell carcinoma (HNSCC). We report the treatment outcomes, adverse events (AEs), and dosimetric parameters in local-regional advanced (LRA) HNSCC patients treated with the WF S-IMRT technique. Methods: The IRB approved this retrospective study. Patients received WF S-IMRT with or without concomitant chemotherapy. Three separate IMRT plans corresponding to 3 planning target volumes were generated. This study reports patient and tumor characteristics, treatment-induced acute AEs based on CTCAE version 3.0, chronic AEs according to RTOG scale and treatment outcomes, local-regional control (LRC), distant metastases (DM), relapse-free survival (RFS), and overall survival (OS). Results: Between January 2003 and December 2010, 103 patients with LRA HNSCC were treated either definitively or postoperatively with WF S-IMRT, with (99 patients) or without (4 patients) concurrent chemotherapy. The median age was 55 years (range, 30 to 89 y). The median cumulative target dose was 70 Gy (range, 60 to 75 Gy). At a median follow-up of 40 months (range, 4 to 95 mo), the 2- and 5-year rates of OS were 94% and 77%, RFS were 90% and 84%, LRC were 97% and 93%, and DM were 9% and 11%, respectively. Grade 3 acute AEs included mucositis (68%), dysphagia (35%), weight loss (19.6%), and xerostomia (7.8%). Chronic worst grade 3 AEs included xerostomia (21.9%), weight loss (12.8%), and dysphagia (12.5%). Chronic grade 3 AEs at last follow-up included weight loss (6.25%), dysphagia (6.2%), and xerostomia (6.2%). No patient had an acute or chronic grade 4 AE, brachial plexopathy, or spinal cord injury. Conclusions: WF S-IMRT results in excellent tumor control and an acceptable toxicity profile in LRA HNSCC patients treated with this technique.